Geochronology, petrogenesis and tectonic settings of pre- and syn-ore granites from the W-Mo deposits (East Kounrad, Zhanet and Akshatau), Central Kazakhstan - Li, G.; Cao, M.; Qin, K.; Evans, Noreen; Hollings, P.; Seitmuratova, E. (Elsevier BV, 2016)
There is significant debate regarding the mineralization ages of the East Kounrad, Zhanet and Akshatau W-Mo deposits of Central Kazakhstan, and the petrogenesis and tectono-magmatic evolution of the granites associated with these deposits. To address these issues, we present molybdenite Re-Os dating, zircon U-Pb dating, whole rock geochemistry as well as Sr-Nd-Pb and zircon O-Hf isotopic analyses on the pre-mineralization and ore-forming granites. U-Pb dating of zircons from pre-mineralization granitic rocks yield Late Carboniferous ages of 320–309 Ma, whereas ore-forming granites have Early Permian ages of 298–285 Ma. Molybdenite Re-Os isotopic data indicate a mineralization age of ~ 296 Ma at East Kounrad, ~ 294 Ma at Akshatau and ~ 285 Ma at Zhanet. The pre-ore and ore-forming granites are high-K calc-alkaline, metaluminous to slightly peraluminous I-type granites. The pre-mineralization granites are relatively unfractionated, whereas the ore-forming granites are highly fractionated. The fractionating mineral phases are probably K-feldspar, apatite, Ti-bearing phases and minor plagioclase. The pre-mineralization and ore-forming rocks are characterized by similar Sr-Nd-Pb-Hf-O isotopic compositions ((87Sr/86Sr)i = 0.70308–0.70501, εNd (t) = − 0.5 to + 2.8, 207Pb/204Pb = 15.60–15.82, zircon εHf (t) = + 1.2 to + 15.6 and δ18O = + 4.6 to + 10.3‰), whole rock TDMC (Nd) (840–1120 Ma) and zircon TDMC (Hf) (320–1240 Ma). The isotopic characteristics are consistent with a hybrid magma source caused by 10–30% assimilation of ancient crust by juvenile lower crust. The geochronology and geochemistry of these granites show that the Late Carboniferous pre-mineralization granitic rocks formed during subduction, whereas the Early Permian ore-forming, highly fractionated granite probably underwent significant fractionation with a restite assemblage of K-feldspar, apatite, Ti-bearing phases and minor plagioclase and developed during collision between the Yili and Kazakhstan terranes commenced at the latest Late Carboniferous.